2014
DOI: 10.1080/17470218.2014.918632
|View full text |Cite
|
Sign up to set email alerts
|

Priming word order by thematic roles: No evidence for an additional involvement of phrase structure

Abstract: Three experiments are reported that studied the priming of word order in German. Experiment 1 demonstrated priming of the order of case-marked verb arguments. However, order of noun phrases and order of thematic roles were confounded. In Experiment 2, we therefore aimed at disentangling the impact of these two possible factors. By using primes that differed from targets in phrase structure but were parallel with regard to the order of thematic roles, we nevertheless found priming demonstrating the critical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 33 publications
8
58
1
Order By: Relevance
“…Further, the magnitude of thematic priming was similar regardless of the presence of animacy cues, suggesting that animacy did not have an independent effect on thematic mapping. These findings are consistent with previous reports of thematic priming in healthy speakers (Chang et al, 2003; Hare & Goldberg, 1999; Köhne et al, 2014; Pappert & Pechmann, 2014; Salamoura & Williams, 2007). …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Further, the magnitude of thematic priming was similar regardless of the presence of animacy cues, suggesting that animacy did not have an independent effect on thematic mapping. These findings are consistent with previous reports of thematic priming in healthy speakers (Chang et al, 2003; Hare & Goldberg, 1999; Köhne et al, 2014; Pappert & Pechmann, 2014; Salamoura & Williams, 2007). …”
Section: Discussionsupporting
confidence: 93%
“…Priming of thematic representations, independent of phrase structure, has been shown for healthy speakers (Bernolet, Hartsuiker, & Pickering, 2009; Carminati, van Gompel, Scheepers, & Arai, 2008; Chang, Bock, & Goldberg, 2003; Hare & Goldberg, 1999; Köhne et al, 2014; Pappert & Pechmann, 2014; Salamoura & Williams, 2007). Chang and colleagues (2003) examined priming of sentences (e.g., 1) which are syntactically similar (NP V NP PP), but differ in the postverbal mapping between thematic roles and syntactic structures (Theme-Location vs. Location-Theme).The authors found that the Theme-Location structure was elicited significantly more frequently following Theme-Location, compared to Location-Theme, primes, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations